Infectious causes of equine respiratory disease on Ontario standardbred racetracks. - Sherman, J (1977)
Upper respiratory disease has been a serious problem in Standardbred horses on racetracks in Ontario, with outbreaks occurring once or twice annually in late winter and early spring seasons. To determine the causes of these epidemics, a 3-year investigation was carried out in which nasal swabs and serum samples were obtained at intervals from apparently healthy horses and from horses suffering from upper respiratory disease. The nasal swabs were used to isolate bacteria and viruses. The serum samples were examined for the presence and level of antibodies to equine influenza viruses and equine herpesvirus 1. None of the bacteria isolated were associated with the outbreaks of disease. Equine herpesvirus 2 was isolated 72 times from both diseased and apparently healthy horses. Equine herpesvirus 1 was isolated 10 times from horses with respiratory disease, both during and between epidemics. Influenza equine/1 virus was isolated seven times and influenza equine/2 was isolated once during severe outbreaks of upper respiratory disease. Serological evidence confirmed that influenza viruses were the causes of the major epidemics, with the equine/1 strain being involved most often.